Living values education program in early childhood - Veryawan, Veryawan; Ningsih, Arie Dwi; Tursina, Ade; Saptiani, Saptiani; Nasution, Raisah Armayanti (Jurnal Anifa: Studi Gender dan Anak, 2023)
Applying appropriate methods to encourage children's growth and development and instilling character values ​​is the main focus of all early childhood education. Many methods and models can be used as references in meeting these requirements. Living Values ​​Education is one of the methods present in society to instill values ​​that focus on students' character. These values ​​are flexible and adapted to needs, culture, and traditions. The research method used is library research, namely a series of research relating to library data collection methods or research whose research objects are explored through various library information. Implementation of Living Values ​​Education that is integrated into the curriculum with twelve fundamental values ​​of love, peace, cooperation, tolerance, sincerity, compassion, respect, honesty, humility, happiness, and unity. A peaceful atmosphere is a whole of rules, order, and peace created in the order of values ​​of life lived with a smile.